2005
DOI: 10.1086/429820
|View full text |Cite
|
Sign up to set email alerts
|

A Biconically Expanding Flow in W43A Traced by SiO Maser Emission

Abstract: We report Very Long Baseline Array and Very Large Array observations of 22 GHz H 2 O and 43 GHz SiO ( , ) maser emission as well as 7 mm continuum emission in W43A, which exhibits a highly v p 1 J p 1-0 collimated jet of molecular gas and a spherically expanding envelope very similar to that of an OH/IR star. The spatiokinematical structure of the H 2 O masers is well fitted to a precessing jet model with an expansion velocity of 150 km s Ϫ1 and a dynamical age of ∼50 yr. The spatiokinematical structure of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
54
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(59 citation statements)
references
References 11 publications
5
54
0
Order By: Relevance
“…v223.-Extreme blue-and redshifted features are present. This star has been imaged previously at OH (1612 MHz), H 2 O (22 GHz), and SiO (43 GHz) maser frequencies ( Imai et al 2002( Imai et al , 2005 confirming the object as a post-AGB source with highvelocity H 2 O jets located outside the shell of OH masers. The H 2 O maser spectrum is highly variable (Likkel et al 1992).…”
Section: Namesupporting
confidence: 62%
“…v223.-Extreme blue-and redshifted features are present. This star has been imaged previously at OH (1612 MHz), H 2 O (22 GHz), and SiO (43 GHz) maser frequencies ( Imai et al 2002( Imai et al , 2005 confirming the object as a post-AGB source with highvelocity H 2 O jets located outside the shell of OH masers. The H 2 O maser spectrum is highly variable (Likkel et al 1992).…”
Section: Namesupporting
confidence: 62%
“…Additionally, interferometric observations of the OH maser region of this class of objects have revealed aspherical morphologies with either equatorial or bi-conical distributions (Amiri et al 2011). High-resolution observations of the SiO masers of the post-AGB object W43A indicates a biconical outflow (Imai et al 2005). The bipolar jets observed in waterfountain sources are related to the onset of asymmetric PNe (Sahai & Trauger 1998).…”
Section: Cse Morphology and Magnetic Fieldmentioning
confidence: 94%
“…Cotton et al 2008;Desmurs et al 2007;Imai et al 2005), and as far as we can tell, no high-resolution VLBI observation has been performed to image SiO masers in OH/IR stars. These objects have larger CSEs and much longer periods up to 2000 days than do Mira variables (Herman & Habing 1985b).…”
Section: Introductionmentioning
confidence: 99%
“…This morphology can not be explained by the standard spherically expanding shell model for the OH maser shells in evolved stars. The dynamical ages of the H 2 O maser jets of W43A & OH 12.8-0.9 are 90 and 50 yr, respectively (Boboltz & Marvel 2007;Imai et al 2005). We measured a shell size of >1600 AU and the expansion velocity of <15 km s −1 for the OH masers.…”
Section: Discussionmentioning
confidence: 99%
“…The H 2 O maser jet has an outflow velocity of ∼145 km s −1 with 39 • inclination from the plane of the sky (Imai et al 2002). The SiO masers of this source are thought to occur in a shock at the interface between the fast collimating jet and the slow biconical outflow (Imai et al 2005). The spatial distribution of the OH maser region of W43A revealed that the OH masers are located inside the H 2 O maser region.…”
Section: W43amentioning
confidence: 92%